2022
DOI: 10.1039/d1na00692d
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the six stages of the current–time curve and the bilayer nanotubes obtained by one-step anodization of Zr

Abstract: The application and growth mechanism of anodic TiO2 nanotubes have been a hot topic in recent ten years, but the formation mechanism of anodic ZrO2 nanotubes is rarely studied. In...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…1b also kept the trend of rising in stage II, and there was no stable anodizing current in stage III, which fully proves that the stability and instability of anodizing current in stage III were not necessarily related to the balance between oxide growth and dissolution. 19,23 Li et al 11 reported that the growth rate of nanotubes is much higher than the rate of oxide dissolution. The anodizing current in stage III keeps rising, as shown in Fig.…”
Section: Current-time Curve Of Anodization Of Titanium In Pure Nh 4 F...mentioning
confidence: 99%
See 1 more Smart Citation
“…1b also kept the trend of rising in stage II, and there was no stable anodizing current in stage III, which fully proves that the stability and instability of anodizing current in stage III were not necessarily related to the balance between oxide growth and dissolution. 19,23 Li et al 11 reported that the growth rate of nanotubes is much higher than the rate of oxide dissolution. The anodizing current in stage III keeps rising, as shown in Fig.…”
Section: Current-time Curve Of Anodization Of Titanium In Pure Nh 4 F...mentioning
confidence: 99%
“…However, these theories cannot clarify three stages of the current-time curve during anodization. [11][12][13][14][15][16][17] Thompson et al 18 concluded that the above field-assisted dissolution reaction does not contribute to the current variation of anodization. They pointed out that the growth rate of oxide is much higher than the rate of oxide dissolution, and it is impossible to keep a balance between oxide growth and dissolution during anodization.…”
Section: Introductionmentioning
confidence: 99%